Students’ Perception of Quipper as an Online Practice Tool for the English Computer-based National Examination - Kirana, Satria Andy (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
This study is a descriptive case study that tries to follow the students’ learning process in using Quipper, an e-learning platform to prepare them for the upcoming Computer-based National Examination. During the length of the research, the students’ perception of Quipper as a practice tool will be gathered and presented, along with the aspects that need to be further developed in the future, and students’ suggestions on how to develop Quipper into an e-learning platform with better functionality. Results of the study revealed that the students have positive perception towards Quipper with several notes about the need to revisit the functionalities and user interface according to what most students would be comfortable with as users. Further, the study also revealed critiques from the students for Quipper’s future developments. Finally, on the basis of the critiques, some suggestions were also given by the students participated in this study. The suggestions consisted of conducting more research on another level of educations besides junior high school to get the overall idea of what the users from all age range need and also the need to conduct research on several other e-learning platforms.